PEMBENTUKAN BUDAYA RELIGIUS TERHADAP MASYARAKAT MINORITAS MUSLIM DI DESA TENGGER KECAMATAN LUMBANG KABUPATEN PROBOLINGGO - Herwati Herwati (LP2M Universitas Ibrahimy, 2022)
This study aims to reveal the formation of religious culture for the Muslim minority community in Tengger Village, Lumbang Probolinggo District. This study uses a descriptive qualitative approach. The results show that the formation of religious culture in the people of Tengger Village, Lumbang Probolinggo is sometimes difficult to implement because they adhere to religion and practice their teachings according to their ancestors. There are also some who think that culture is very contrary to religion because the religious culture that comes is not in accordance with the teachings of their religion. The activities in the formation of religious culture include routine recitations held at the village level, RT level and RW level in the form of Islamic studies, tahlilan, sholawatan and istighosah. Pesantren educational institutions, formal and non-formal, Islamic institutions (NU, Anshor and Muhammadiyah) also play an active role in shaping the religious culture of the community. Supporting factors in the formation of religious culture; 1. Some residents have a very high religious level (the heads of families of the village Muslim community are fanatical about religious teachings), 2. Routine activities programmed by the village such as joint tea, yasinan, sholawatan, istighosah etc., 3. The community (individuals) have an understanding and high level of awareness of religious activities in the village. While the inhibiting factor; 1. The development of technology is very rapid, 2. The number of people who imitate non-Muslim habits, 3. The lack of public awareness of the importance of religious programs held in the village.